Unpacking The Unforeseen Consequences: A Comprehensive Examination on The Perception of Non-Profit Organisations on Goods and Services Tax - Vedamuthu, Lawrence Benadict; K, Chellapandian; I A, Ahamed Wasim Musthaq (South India Journal of Social Sciences, 2025)
This study examines Indian Non-Profit Organizations’ (NPOs) perceptions of the Goods and Services Tax (GST), focusing on compliance challenges and operational implications. Using mixed methods, primary data from 110 Tamil Nadu NPOs via structured questionnaires were analyzed alongside secondary sources. Descriptive statistics, reliability tests (Cronbach’s α = 0.897–0.898), t-tests, and ANOVA assessed awareness levels, compliance burdens, and demographic influences. Results indicate GST imposes significant challenges for NPOs, particularly smaller entities, due to ambiguous tax applicability for dual activities (charitable/commercial), stringent documentation, and limited input tax credits. While 59% of NPOs remained unregistered, registered ones reported increased tax liabilities (41%) and administrative strain. However, GST enhanced transparency, bolstering donor trust. Demographic analysis revealed age (p=0.040) and education (p=0.035) as key factors shaping GST perceptions, while gender and legal status showed negligible impact. The study highlights systemic gaps in GST frameworks, including complex compliance processes and insufficient sector-specific guidance. It advocates streamlined filing procedures, exemptions for non-commercial activities, and training initiatives to improve regulatory adaptability. By addressing empirical gaps in taxation research, this work provides policymakers with insights to align GST norms with NPOs’ operational realities. Findings underscore the urgency of collaborative dialogue between regulators and NPOs to reduce compliance inefficiencies and strengthen the sector’s socio-economic contributions. Such reforms would ensure GST supports, rather than hinders, NPOs’ public welfare missions while fostering equitable fiscal governance.